Psychosocial Predictors of Healthcare Decision-Making Capacity in Older Adults: The Role of Cognitive Functioning and Affective Symptoms - Emília Santos; Ana S. Amaral; Rosa M. Afonso (Healthcare, 2026)
Background/Objectives: The capacity for decision-making in healthcare is a critical component of autonomy in later life; however, its psychosocial determinants remain insufficiently understood. This study aimed to examine the relationship between decision-making capacity in healthcare, cognitive functioning, depressive and anxiety symptoms, and sociodemographic factors in cognitively healthy older adults, and to identify psychosocial predictors of capacity for decisions. Methods: A cross-sectional study was conducted with 60 older adults. Participants completed measures for decision-making capacity in healthcare, cognitive performance, depressive symptoms, and anxiety symptoms. Spearman correlations and multiple linear regression analyses were performed. Regression assumptions were formally tested, and sensitivity analyses were conducted. Results: The capacity decision-making in healthcare was positively associated with cognitive performance but not significantly correlated with depressive or anxiety symptoms. Regression analyses revealed that age and depressive symptomatology were significant negative predictors, with the model explaining 44.9% of the variance (adjusted R2 = 0.375). Sensitivity analyses indicated that the age effect was stable across all specifications, whereas the contribution of depressive symptomatology was concentrated among a few participants with clinically elevated symptoms. Anxiety symptoms were not significant predictors. A strong positive association was observed between depressive and anxiety symptoms. Conclusions: These findings support a multidimensional model of the capacity for decision-making in healthcare, highlighting the central role of cognitive functioning and age, and suggesting that depressive symptoms may become clinically relevant at higher symptom levels, even in cognitively healthy older adults. The results underscore the importance of integrating cognitive and emotional assessment in capacity evaluations and suggest that addressing depressive symptoms may contribute to preserving decisional autonomy. Future research should adopt longitudinal and clinically diverse samples to further elucidate these relationships.